Rapid preparation of bioactive composites for transforaminal lumbar interbody fusion - Baozhi Ding; Xin Wang; Changqing Zhao; Jie Zhao (Scientific Reports)
Abstract The current stem cell tissue engineering always requires in vitro cell culture. To solve this problem, the bone mesenchymal stem cells (MSCs) screen-enrich-combine circulating system (SECCS) was created to rapidly enrich stem cells and combined with β-tricalcium phosphate (β-TCP) to immediately produce bioactive MSCs/β-TCP composites. 37 patients who underwent transforaminal lumbar interbody fusion (TLIF) surgery were included in this study and randomly divided into two groups. One group uses laminal bone grafts (LBG) for intervertebral fusion, and another group uses MSCs/β-TCP composites. The new technique could quickly and selectively enrich stem cells from the bone marrow and simultaneously implant them into the intervertebral space during operation. The cells eluted from the β-tricalcium phosphate were confirmed to be stem cells based on their characteristics. Higher early fusion rates, similar intervertebral height decreases, and functional improvement tendencies were observed in the SECCS group when compared to the LBG group. The bioactive scaffold prepared by SECCS showed better osteogenic efficiency at the early stage of intervertebral fusion compared to autologous LBG, which provided a new bone scaffold substitute for autologous bone.